Visual Identification and Serotyping of Toxigenic Vibrio cholerae Serogroups O1 and O139 With CARID - Lu, Pan; Chen, Jialiang; Li, Zhenpeng; Li, Zhe; Zhang, Jingyun; Kan, Biao; Pang, Bo (Frontiers in Cellular and Infection Microbiology, 2022)
There is a growing demand for rapid, sensitive, field-deployable nucleic acid tests for cholera, which usually happens in rural areas. In this study, we developed a Cas12a-assisted rapid isothermal detection (CARID) system for the detection of toxigenic V. cholerae serogroups O1 and O139 by combining recombinase-aided amplification (RAA) and CRISPR-Cas (clustered regularly interspaced short palindromic repeats and CRISPR-associated proteins). The results can be determined by fluorescence signal and visualized by lateral flow dipstick (LFD). We identified 154 V. cholerae strains and 129 strains of other intestinal diarrheagenic bacteria with a 100% coincidence rate. The limit of detection of CARID was 20 copies/reaction of V. cholerae genomic DNA, which is comparable to that of polymerase chain reaction (PCR) and qPCR. Multiple-CARID was also established for efficiency and economic considerations with an acceptable decrease in sensitivity. Simulating samples' test showed that CARID is suitable for complex samples. In conclusion, CARID is a rapid, sensitive, economically efficient, and portable method, which makes it suitable for a field response to cholera.